Witness for the persecution eaudiobook - Copperman, E. J. (Jersey Girl Legal Mystery, 2022)
Movie premiers, murder charges, and celebrity shenanigans? It's all in a day's work for New Jersey prosecutor turned LA family lawyer Sandy Moss. Former New Jersey prosecutor Sandy Moss moved to a prestigious Los Angeles law firm to make a new start as a family lawyer. So it seems a little unfair that Seaton, Taylor have created a criminal law division specifically for her. Just because she's successfully defended two murder trials, it doesn't mean she likes them! But when abrasive Hollywood movie director Robert Reeves is accused of murdering a stuntman on set, Sandy finds she can't say no when he demands her help. Robert might be an unpleasant, egotistical liar, but something tells Sandy that he's innocent—even if no one else can see it. At least this time, she reassures herself, her charismatic, adorable, and oh so annoying TV star boyfriend Patrick McNabb isn't involved in the case. He isn't ... right? The third in the fast-paced, funny, legal mystery series starring pitch-perfect heroine Sandy Moss, who "could give Perry Mason a run for his money" (Kirkus Reviews), is a great pick for fans of cozy mysteries, legal dramas, and anyone who likes to laugh!